Effect of slice thickness on the acceptability of fish crackers ('keropok') - Yu, Swee Yean (John Wiley & Sons, 1993)
Fish crackers ('keropok') were prepared according to the modified method of Siaw, Idrus and Yu (1985). The keropok was sliced to thicknesses of 1·0, 1·5, 2·0, 2·5, 3·0, 3·5 and 4·0 mm and expanded by frying in hot oil. Results indicated that linear expansion was not affected by the thickness of the keropok slice; however, sensory evaluation showed that slices of 3 and 3·5mm were most acceptable. Panellists commented that thickness was important for correct mouthfeel.